Plastic Film and Packaging Waste Management in Southwestern Ontario: An analysis of current diversion patterns and trends - Lim, Amanda Yan Yan (University of Waterloo, 2021)
The production of plastics has drastically grown through the years. In the age of convenience, single use plastics (especially film) have become ubiquitous in everyday life and so has its waste. Plastic waste can be found in unintended places such as in our oceans, animals and even in our food. While plastic film packaging is economically beneficial to many businesses due to their lightweight nature and durability, these same characteristics severely damage our environment and ecosystems from production to disposal. Recycling plastic waste is a common scapegoat used to excuse plastic production, however, not all plastics can be recycled and mismanaged plastic waste poses a great threat to the environment when they blow and pollute surrounding areas. A circular economy must be generated to reduce the amount of virgin plastic film produced, and waste in our environment. To decrease environmental impacts, the entire plastic life cycle needs to be analyzed to determine the true cost of plastic use from fossil fuel reliance in production to environmental degradation from mismanaged plastic waste during disposal. The Canadian government has announced their intent to eliminate single use plastics, however, this is a slow-moving initiative and plastic waste produced to date still remains in the environment and there is no immediate halt on single use plastic production. A gap in knowledge exists when it comes to determining and evaluating an optimal strategy in a Canadian landscape. This thesis will answer the research question “What are the challenges and opportunities associated with a circular economy approach to plastic packaging and film waste management?”. Global case studies from successful circular economies (UK, Rwanda, Philippines) are examined to identify key criteria that need to be met to encourage this transition. In addition, this thesis will break down popular strategies found in academic literature and industry (reduction of waste downstream, expanding recovery systems and extended producer responsibility) through 6 key stakeholder interviews and further identify how various aspects of each can play a role in the transition towards a circular economy while considering external legislative, social and economic factors. Using key interventions as determined in the Economic Study of the Canadian Plastic Industry Markets and Waste report conducted by Environment and Climate Change Canada (2019) as a guide, interview questions were developed to identify the practicality of each according to industry experts to provide insight on how to best move forward with an implementation plan. By conducting a detailed analysis on the practicality and feasibility of current proposed interventions, barriers towards circularity were identified. The plastic crisis is largely driven by linear business models, and sustained due to the lack of consensus on how to best solve it. A circular economy requires an innovative sustainable plastics industry which is achieved through support from government, industry and citizens. At the start of life cycle, government intervention plays a key role in determining the amount of plastic waste that circulates within the environment. Numerous actions can be taken to reduce this however, with a majority focus on levelling the playing field between virgin resin producers and post consumer resin producers. Stricter enforcements within industry requiring minimum recycled content in production and funding sustainable alternatives are key actions that need to be undertaken. A circular economy strategy places an emphasis on maximizing the life span of plastics produced already. A focus should be placed on implementing extended producer responsibility at the end-of-life cycle (using economic instruments to deter industry from disposing plastic waste that can be recycled), as well as investing in educational outreach to create public awareness on the detrimental effects of overconsumption to citizens. This thesis acts as a summary of best practices to adapt within a Southwestern Ontario/Canadian landscape, while adding additional context to plastic film and packaging waste management to public knowledge. While it is up to governments to listen to public needs, without citizen action, there will be nothing pushing legislation to recognize the issue. Advocacy starts with the citizen. Increased public knowledge on the problematic nature of plastic film production, consumption and disposal may spark progressive action. Future opportunities for research should look to address the role of key value chains in the plastic life cycle and fossil fuel reliance.
Keywords: Plastic Film; Waste Management; Recycling; Stakeholder Analysis; Plastic Packaging; Waste Strategy